2015
DOI: 10.1590/1414-431x20154460
|View full text |Cite
|
Sign up to set email alerts
|

Low-intensity red and infrared laser effects at high fluences on Escherichia coli cultures

Abstract: Semiconductor laser devices are readily available and practical radiation sources providing wavelength tenability and high monochromaticity. Low-intensity red and near-infrared lasers are considered safe for use in clinical applications. However, adverse effects can occur via free radical generation, and the biological effects of these lasers from unusually high fluences or high doses have not yet been evaluated. Here, we evaluated the survival, filamentation induction and morphology of Escherichia coli cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
0
9
1
3
Order By: Relevance
“…локальной температуры в окрестности наночастицы и средней температуры суспензии представлены в работах [27,28]. Этот механизм лежит в основе повреждений, возникающих в клетке, и влечет за собой ее гибель [1][2][3][4][5][6]10,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. В ходе данного исследования показано, что два типа ЗНЧ (нанокубики и наностержни) вызывали дозозависимое сокращение численности бактериальных популяций под действием излучения с мощностью 60 mW/сm 2 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…локальной температуры в окрестности наночастицы и средней температуры суспензии представлены в работах [27,28]. Этот механизм лежит в основе повреждений, возникающих в клетке, и влечет за собой ее гибель [1][2][3][4][5][6]10,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. В ходе данного исследования показано, что два типа ЗНЧ (нанокубики и наностержни) вызывали дозозависимое сокращение численности бактериальных популяций под действием излучения с мощностью 60 mW/сm 2 .…”
Section: Discussionunclassified
“…Лазерное излучение с интенсивностью порядка 3000−4000 mW/сm 2 способно привести к обезвоживанию, коагуляции белков, изменению заряда молекул, в частности ключевых ферментов клетки. При этом повреждения затрагивают и ДНК, и ферментативный аппарат, необходимый для ее репарации и восстановления [29].…”
Section: Discussionunclassified
“…The physiological mechanism of LLLT has been adequately established in cellular experiments. LLLT has been used in culture experiments, in which it affects the survival of plasmids in Escherichia coli cells, and DNA repair was produced by pulsed emission modes through low-level infrared laser action [ 25 ]. Furthermore, AlGhamdi et al demonstrated that LLLT is useful in enhancing the proliferation rate of cell lines [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…LLLT which is commonly known as Low Level Laser therapy is as a potent modality of treatment for controlling the growth of Gram positive and Gram negative bacteria ( Barboza et al, 2015 , Dixit et al, 2019 , Nussbaum et al, 2002 ). As they are low-cost devices and are progressively being used in health care system.…”
Section: Introductionmentioning
confidence: 99%
“…As they are low-cost devices and are progressively being used in health care system. It is usually postulated that absorption of laser light through chromophores causes alterations in cell physiology eventually leading to cascade of events resulting in cell damage of the bacteria’s ( Barboza et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%